ChemInform Abstract: Chemoselective Oxidation by Electronically Tuned Nitroxyl Radical Catalysts. Issue 50 (10th December 2013) - Hamada, Shohei; Furuta, Takumi; Wada, Yoshiyuki; Kawabata, Takeo
Abstract The nitroxyl radical shown in the scheme is found to be an efficient catalyst for the oxidation of secondary alcohols.